2017
DOI: 10.1136/oemed-2017-104505
|View full text |Cite
|
Sign up to set email alerts
|

3-(Bromomethyl)-2-chloro-4-(methylsulfonyl)- benzoic acid: a new cause of sensitiser induced occupational asthma, rhinitis and urticaria

Abstract: We identified a new low molecular weight agent causing occupational asthma, rhinitis and contact urticaria. A typical clinical picture of allergic diseases and positive skin prick tests suggest underlying IgE-mediated disease mechanisms. Stringent exposure control measures are needed in order to prevent BCMBA-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Additionally, it facilitates comparison of epidemiological results. Recent population-based studies and clinical trials utilise one of the aforementioned testing methods each: Sovij€ arvi [30][31][32][33][34][35][36][37], Malmberg [38][39][40][41] or Nieminen [14,[42][43][44]; the reference table may serve the purpose of offering comparisons in these example studies and others, or in future studies. Nowadays, the supply of histamine as a challenge test substance is very limited, therefore, a comparison to other challenge methods was also needed.…”
Section: Utilitymentioning
confidence: 99%
“…Additionally, it facilitates comparison of epidemiological results. Recent population-based studies and clinical trials utilise one of the aforementioned testing methods each: Sovij€ arvi [30][31][32][33][34][35][36][37], Malmberg [38][39][40][41] or Nieminen [14,[42][43][44]; the reference table may serve the purpose of offering comparisons in these example studies and others, or in future studies. Nowadays, the supply of histamine as a challenge test substance is very limited, therefore, a comparison to other challenge methods was also needed.…”
Section: Utilitymentioning
confidence: 99%
“…Reviews of compensated claims for work-related asthma and clinic reviews have suggested a reduction over the past few years in rates of recognized occupational asthma in several jurisdictions, such as in Canada, France and England,234 possibly due to preventive measures. However, new causes of occupational asthma continue to be reported 5678. In addition, general population studies continue to suggest relatively high rates of work-related asthma accounting from 15% of adult asthmatics in a US survey,910 up to 33% of adult asthmatics who reported work-related aggravation of asthma in a British postal survey (though the overall response rate was low at 13%) 11.…”
Section: Introductionmentioning
confidence: 99%
“…O mecanismo fisiopatológico envolvido na indução de asma ocupacional por agentes de baixo peso molecular permanece amplamente desconhecido (MAESTRELLI et al, 2009). Sabe-se que na maioria dos casos o mecanismo é IgE independente, como o caso do epoxi amina (VANDENPLAS et al, 2017), contudo, alguns dos agentes de baixo peso também induzem asma com mecanismo IgE dependente, como é o caso do 3-Bromo Metil-2-cloro-4-(metil Sulfonil) -ácido benzoico (SUOJALEHTO et al, 2018).…”
Section: Asma Relacionada Ao Trabalhounclassified
“…Exemplos de trabalhadores com elevado risco de desenvolvimento de asma induzida pela exposição a irritantes químicos incluem, profissionais de área da saúde, principalmente fisioterapeuta respiratório, enfermeiros e terapeutas ocupacionais (ARIF; DELCOS, 2012); pessoal de serviço de limpeza (ARIF et al, 2003; ZOCK; VIZCAYA; LE MOUAL, 2010); trabalhadores envolvidos na fabricação de produtos químicos (SUOJALEHTO et al, 2018); pessoas que trabalham com revestimento contendo epóxi (VANDENPLAS et al, 2017). O primeiro passo para o diagnóstico de asma relacionada ao trabalho é a confirmação clínica de que o paciente realmente tem asma.…”
Section: Asma Relacionada Ao Trabalhounclassified